Panorama dos resíduos sólidos urbanos nos municípios de pequeno porte do Brasil - Arcila, Rafaella Iliana Alves (2008)
The panorama of Urban Solid Waste (USW) in Brazil, in general lacks information, given the immensity of the country. However, it is from available data that the public executives should define the USW management. To contribute to the choice of a model for the management of USW in small municipalities, this study reviews the related literature, showing an overview of the final disposal of USW in small municipalities. Several data and researches are discussed, concluding that the available data, despite being provided by the public managers, who often attenuate the problem, should be considered for the proposition of policies to encourage the waste treatment